PR TOOLS TO MANAGE THE REPUTATION OF THE COMPANY ON THE INTERNET - I. Makhonina; A. Gladysheva; I. Chepurova (Вестник Северо-Кавказского федерального университета)
The process offorming a positive reputation of a company in the global network acquires particular relevance for business in modern conditions. Online reputation management allows a company to create a positive online image, build loyalty to the company, and minimize negativity. As a result, the necessity of forming a positive reputation of the company on the Internet was justified. First, the theoretical relationship between PR tools and a company's reputation in the global network is studied. Secondly, the main stages of reputation management, PR tools, as well as the main components of a company's positive reputation are analyzed. Third, the effectiveness of the company's positive and negative reputation is calculated. There was revealed a contradiction in Russian and international standards in relation to the value of reputation (goodwill), which required convergence of accounting standards.